Penerapan Standar Keselamatan Wisata Pantai Melalui Edukasi P3K pada Pengelola Wisata Pantai Lumpue - Ni Ny. Wedarthani Achintya A.; Bhirau Wilaksono; Diah Astini Paramitha; Ega Delva; Nurul Azizah; Tamina Melindah (Jurnal Informasi Pengabdian Masyarakat, 2026)
Marine tourism in Indonesia has experienced rapid growth but is not accompanied by an increase in tourist safety standards. Lumpue Beach in Parepare City is a tourist destination that attracts many visitors, but the Lumpue beach management does not yet have First Aid (P3K) capacity. The Community Service (PKM) activity aims to improve health literacy and tourist safety standards at Lumpue Beach through First Aid education. This activity uses a community service with educational method for 180 minutes at the Parepare Campus. The number of participants is 15 people. The education used poster media and was followed by a semi-informal discussion. Evaluation of the level of understanding used a pre-test and post-test which were analyzed descriptively quantitatively with indicators of success of a minimum score increase of 20% and a minimum post-test achievement of 80% as well as the ability to simulate First Aid. The results of the education showed a score increase of 68.57% from 52.5 (pre-test) to 88.5 (post-test). The results of interviews and simulations showed that participants understood the concept and were able to practice First Aid procedures well. Structured education based on visual media and simulations has proven effective in improving Lumpue Beach management's preparedness for handling tourist accidents. Further recommendations include conducting periodic evaluations every 1-3 months to ensure participants' skills are maintained.